Effects of welding parameters and post-heat treatment on mechanical properties of friction stir welded AA2195-T8 Al-Li alloy. Issue 1 (January 2018) - Zhang, J.; Feng, X.S.; Gao, J.S.; Huang, H.; Ma, Z.Q.; Guo, L.J.
Abstract: In this study, the effects of main welding parameters (rotation speed ( ω ) and welding speed ( v )) on the microstructure, micro-hardness distribution and tensile properties of friction stir welded (FSW) 2195-T8 Al-Li alloy were investigated. The effects of T6 post-treatments at different solution and aging conditions on the mechanical properties and microstructure characteristics of the FSW joints were also investigated. The results show that with increasing ω and v, both strength and elongation of the joints increase first, and then decrease with further increase of ω and v . All the joints under varied welding parameters show significant strength loss, and the strength reaches only 65% of the base metal. The effect of T6 post-heat treatment on the mechanical properties of the joints depends on the solution and aging conditions. Two heat treatment processes (480 °C × 0.5 h quenching + 180 °C × 12 h, 520 °C × 0.5 h quenching + 180 °C × 12 h aging) are found to increase the joint strength. Furthermore, low temperature quenching (480 °C) is more beneficial to the joint strength. The joint strength can reach 85% of the base metal. Whereas both low temperature aging (140 °C × 56 h) and stepped aging (100 °C × 12 h + 180 °C × 3 h) processes decrease the joint strength. After heat treatment all the joints show decreased ductility due to the obvious grain coarsening in the nugget zone (NZ) and thermo-mechanically affected zone (TMAZ).